Sequence meets function—microbiota and cardiovascular disease. Issue 2 (4th February 2021) - Kim, Myungsuk; Huda, Md Nazmul; Bennett, Brian J
Abstract: The discovery that gut-microbiota plays a profound role in human health has opened a new avenue of basic and clinical research. Application of ecological approaches where the bacterial 16S rRNA gene is queried has provided a number of candidate bacteria associated with coronary artery disease and hypertension. We examine the associations between gut microbiota and a variety of cardiovascular disease (CVD) including atherosclerosis, coronary artery disease, and blood pressure. These approaches are associative in nature and there is now increasing interest in identifying the mechanisms underlying these associations. We discuss three potential mechanisms including: gut permeability and endotoxemia, increased immune system activation, and microbial derived metabolites. In addition to discussing these potential mechanisms we highlight current studies manipulating the gut microbiota or microbial metabolites to move beyond sequence-based association studies. The goal of these mechanistic studies is to determine the mode of action by which the gut microbiota may affect disease susceptibility and severity. Importantly, the gut microbiota appears to have a significant effect on host metabolism and CVD by producing metabolites entering the host circulatory system such as short-chain fatty acids and trimethylamine N-Oxide. Therefore, the intersection of metabolomics and microbiota research may yield novel targets to reduce disease susceptibility. Finally, we discuss approaches to demonstrate causality such as specific diet changes, inhibition of microbial pathways, and fecal microbiota transplant.